2016
DOI: 10.1891/0886-6708.vv-d-14-00194
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Analysis of the Criminal Careers of Intimate Partner Violence Offender Subtypes: Results From a Prospective Survey of Males

Abstract: Using data from the Cambridge Study in Delinquent Development, a prospective longitudinal survey of more than 400 males in the United Kingdom followed from age 8 years to age 48 years, we investigated the role of Cluster B personality traits and the association with violent offending groups based on a typology theory of male intimate partner violence (IPV) perpetrators: those who committed family-only violence and the generally violent offender. We also considered whether offending/violent groups could be pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 77 publications
0
12
1
2
Order By: Relevance
“…Though studies are suggesting that violence is not exclusive to men, but that women could also be perpetrators (Sommers, 1994 ; Ristock, 2002 ; Belknap et al, 2012 ), data from the World Health Organization (WHO) are clear in suggesting that women are more likely than men to be the target of violence (Stewart, 2002 ; ISTAT, 2006 ), of sexual abuse (Zara, 2018 ), of psychological abuse (Pico-Alfonso, 2005 ), of domestic violence (Johnson and Ferraro, 2000 ; Lloyd et al, 2017 ), of intimate partner violence (Theobald et al, 2016 ). This could be also a result of women becoming more open about the problems than men, hence they are more likely to report the abuse and violence than men are (Dutton, 2010 ), and this may be more so the younger the people involved (Capaldi et al, 2012 ; Kim et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though studies are suggesting that violence is not exclusive to men, but that women could also be perpetrators (Sommers, 1994 ; Ristock, 2002 ; Belknap et al, 2012 ), data from the World Health Organization (WHO) are clear in suggesting that women are more likely than men to be the target of violence (Stewart, 2002 ; ISTAT, 2006 ), of sexual abuse (Zara, 2018 ), of psychological abuse (Pico-Alfonso, 2005 ), of domestic violence (Johnson and Ferraro, 2000 ; Lloyd et al, 2017 ), of intimate partner violence (Theobald et al, 2016 ). This could be also a result of women becoming more open about the problems than men, hence they are more likely to report the abuse and violence than men are (Dutton, 2010 ), and this may be more so the younger the people involved (Capaldi et al, 2012 ; Kim et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A criminogenic environment increased the risk of IPV by fostering the development of antisocial behavior and neuropsychological deficits, suggesting that IPV is never a private matter, but that the nature and quality of the relationship, along with individual and familial factors, contributed to IPV. Other studies using CSDD data advocated that processes of discontinuity and continuity between childhood and adolescent risk factors seem to increase the likelihood of future involvement in IPV by male partners (Theobald and Farrington, 2012 ), and between generations, though with some differences in risk factors for males and females (Theobald et al, 2016 ). Hence, the acknowledgment that IPV is not just situational, contextual and cultural is scientifically recognized.…”
Section: Introductionmentioning
confidence: 99%
“…De leur côté, les études orientées vers l'agresseur tendent à conclure qu'il existe certains points communs entre les auteurs de violence conjugale. Les hommes plus âgés (Hayes, 2015) et les personnes qui présentent une consommation d'alcool abusive (Devries et al, 2013 ;Ouellet et Cousineau, 2014 ;Piquero, Theobald et Farrington, 2014), qui possèdent des antécédents criminels (Ouellet et al, 2017 ;Ouellet et Cousineau, 2014 ;Ouellet, Paré, Boivin et Leclerc, 2016 ;Piquero et al, 2006) et qui présentent une personnalité antisociale (Theobald, Farrington, Coid et Piquero, 2016 ;Theobald, Farrington, Ttofi et Crago, 2017), sont davantage à risque d'être auteurs de violence conjugale. Kingsnorth (2006) présente une étude sur la récidive des auteurs de violence conjugale dans laquelle il analyse simultanément des caractéristiques sociodémographiques et judiciaires de l'agresseur.…”
Section: Les Facteurs De Risqueunclassified
“…Au même titre que les circonstances de vie immédiates, la violence conjugale n'est pas nécessairement stable et une analyse du contexte permet de mieux comprendre les facteurs précipitants de la violence et les facteurs qui contribuent à la manifestation de celle-ci (Yoshihama et Bybee, 2011). Des études laissent entendre qu'à court terme certaines circonstances de vie tels les épisodes de consommation d'alcool (Devries et al, 2013 ;Quigley et Leonard, 1999 ;Sinha, 2013), la perte d'un emploi (Hayes, 2015 ;Ouellet et Cousineau, 2014), la cohabitation avec le partenaire intime (Johnson, 2008 ;Theobald et al, 2016 ;Winstok, 2013), la présence de violence psychologique (Winstok, 2008) et la séparation (Hayes, 2015 ;Kim et Gray, 2008) peuvent influencer les comportements violents en contexte conjugal. Or, aucune étude empirique portant spécifiquement sur la violence conjugale n'a pu démontrer ces liens.…”
Section: Les Facteurs De Risqueunclassified
“…Earlier, Lussier et al (2009) showed how antisocial behavior in adolescence and low verbal intelligence led to IPV at age 48. Theobald et al 2016b, c) compared risk factors for males who were violent both inside and outside the home with risk factors for males who were only violent in one setting. The generally violent males tended to be worse on psychopathy, personality disorders, and life success.…”
mentioning
confidence: 99%